Ultrasound of the Small Bowel in Crohn’s Disease - Emma Calabrese; Francesca Zorzi; Francesco Pallone (International Journal of Inflammation)
Several radiological and endoscopic techniques are now available for the study of inflammatory bowel diseases. In everyday practice, the choice of the technique to be used depends upon its availability and a careful evaluation of diagnostic accuracy, clinical usefulness, safety, and cost. The recent development of innovative and noninvasive imaging techniques has led to a new and exciting area in the exploration of the gastrointestinal tract, especially in Crohn’s disease patients by using ultrasound with oral or intravenous contrast.